Addressing the Underrepresentation of African American Mental Health Professionals: A Call to Action - Victor Ajluni MD; Georgia Michalopoulou PhD (Journal of Patient Experience)
The mental health workforce in the United States faces a significant challenge: a stark underrepresentation of African American practitioners. This disparity reflects broader issues of racial inequality in healthcare and has far-reaching implications for mental health care delivery, particularly within Black communities. This perspective examines the contributing factors to this underrepresentation, explores its consequences on patient care and research, and proposes strategies to increase diversity in the field. By addressing this issue, we can work towards a more equitable, effective, and culturally responsive mental health care system for all.